Assessment of Streptococcus mutans biofilm formation on calcium phosphate ceramics: The role of crystalline composition and microstructure - Hympánová, Michaela; Oliver-Urrutia, Carolina; Vojta, Marek; Macháček, Miloslav; Krupka, Pavel; Kukla, Rudolf; Celko, Ladislav; Montufar, Edgar B; Marek, Jan (Biomaterials advances, 2022)
Streptococcus mutans is one of the bacteria that initiates the colonization of the pellicle at the tooth surface. It forms a plaque, together with other bacteria, which gradually dissolves the pellicle and leaves the tooth surface unprotected against the acidic oral environment. Calcium phosphate ceramics are excellent synthetic materials for the study of biofilm formation in dentistry because they are comparable to teeth in chemical composition and structure. Calcium phosphates can be processed to achieve a variety of crystalline compounds with biologically relevant ionic substitutions and structures that allow study of the effect of the surface chemistry and the topography independently. In this article, we describe the preparation and characterization of three types of calcium phosphate-based materials as a suitable surface for the formation of the S. mutans biofilm: beta-tricalcium phosphate (β-TCP); sintered hydroxyapatite (SHA); and calcium-deficient hydroxyapatite (CDHA). The densest biofilms were formed on the surfaces of SHA and CDHA, with no significant differences due to the stoichiometry or microstructure. In contrast, β-TCP showed a lower susceptibility to S. mutans biofilm formation, suggesting that the crystalline structure is the controlling parameter. Subsequently, SHA was selected to develop a dental biofilm model that allowed study of S. mutans biofilm susceptibility to chlorhexidine and ethanol.
Keywords: hydroxyapatit; Calcium Phosphates; Durapatite; fosforečnany vápenaté; Streptococcus mutans; biofilmy; Ceramics; keramika; Biofilms